A Pentecostal perspective on the use of Psalms of Lament in worship - Maré, Leonard P. (Verbum et ecclesia, 2008)
The idea of lament as part of human worship experience is foreign within the Pentecostal tradition. This is the case not only in Pentecostal literature, but also in Pentecostal liturgy. This negative viewpoint regarding the place of lament in worship goes hand in hand with the negativity towards the whole of the Old Testament within the Pentecostal tradition. Pentecostals usually regard the New Testament as more applicable to the life and worship of the Church. This viewpoint is in contrast with Pentecostal hermeneutics, with its emphasis on "shared experience". The aim of this paper is to show that lament should be part and parcel of Pentecostal worship. Guidelines on how lament can be utilised in the Pentecostal Church are presented.